Efficient no‐glycerol biodiesel production using a novel biotemplated hierarchical porous‐structure CaO(O). Issue 5 (24th January 2020) - Tang, Ying; Yang, Ying; Liu, Huan; Li, Zhaoyi; Zhang, Jie; Zhang, Zhifang
Abstract: BACKGROUND: In order to obtain an effective solid base with high surface area and hierarchical distribution of pore size, CaO(O) was synthesized via an exotemplating method, using radish as template and calcium acetate as precursor. RESULTS: The CaO(O) obtained by calcination of the impregnated biomorphic template demonstrated effective catalytic activity for the coupling transesterification of vegetable oil to produce biodiesel under mild reaction conditions using tri‐components (methanol, oil and methyl acetate) as resources. High yield of biodiesel, 98.6%, was obtained with a molar rapeseed oil/methyl acetate/methanol ratio of 1:1:8 under 65 °C at 2 h, which is greatly shorter than 6 h over commercial calcium oxide (CaO). CONCLUSION: Various techniques including nitrogen physical adsorption, X‐ray diffraction (XRD), Fourier‐transform infrared (FTIR), thermogravimetric (TG), carbon dioxide‐chemical adsorption and morphology have been employed to characterize the samples. These results demonstrated that the synthesized CaO derived from plant template has a large surface area and various pore diameter distribution which cause hierarchical basic sites over the solid base. © 2020 Society of Chemical Industry